Preterm birth and metabolic implications on later life: A narrative review focused on body composition - Casirati, Amanda; Somaschini, Alberto; Perrone, Michela; Vandoni, Giulia; Sebastiani, Federica; Montagna, Elisabetta; Somaschini, Marco; Caccialanza, Riccardo (Frontiers in Nutrition, 2022)
Preterm newborn infants are characterized by low body weight and lower fat mass at birth compared with full-term newborn neonates. Conversely, at term corrected age, body fat mass is more represented in preterm newborn infants, causing a predisposition to develop metabolic syndrome and cardiovascular diseases on later life with a different risk profile in males as compared with females. Postnatal growth is a complex of changes in anthropometric parameters and body composition. Both quantity and quality of growth are regulated by several factors such as fetal programming, early nutrition and gut microbiota. Weight gain alone is not an optimal indicator of nutritional status as does not accurately describe weight quality. Analysis of body composition represents a potential useful tool to predict later metabolic and cardiovascular risk as it detects the quality of growth by differentiating between fat and lean mass. Longitudinal follow-up of preterm newborn infants could take advantage of body composition analysis in order to identify high risk patients in whom apply early preventive strategies. The aim of this narrative review was to examine the state of the art regarding the body composition among born preterm children, with a focus on those aged as pre-schoolers.